Biomarkers of Cardiovascular Risk in Patients With Rheumatoid Arthritis: Results From the TARGET Trial - Daniel H. Solomon; Olga Demler; Pamela M. Rist; Leah Santacroce; Ahmed Tawakol; Jon T. Giles; Katherine P. Liao; Joan M. Bathon (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Cardiovascular disease remains an important comorbidity in patients with rheumatoid arthritis (RA), but traditional models do not accurately predict cardiovascular risk in patients with RA. The addition of biomarkers could improve prediction. Methods and Results The TARGET (Treatments Against RA and Effect on FDG PET/CT) trial assessed whether different treatment strategies in RA differentially impact cardiovascular risk as measured by the change in arterial inflammation on arterial target to background ratio on fluorodeoxyglucose positron emission tomography/computed tomography scans conducted 24 weeks apart. A group of 24 candidate biomarkers supported by prior literature was assessed at baseline and 24 weeks later. Longitudinal analyses examined the association between baseline biomarker values, measured in plasma EDTA, and the change in arterial inflammation target to background ratio. Model fit was assessed for the candidate biomarkers only, clinical variables only, and models combining both. One hundred nine patients with median (interquartile range) age 58 years (53–65 years), RA duration 1.4 years (0.5–6.6 years), and 82% women had biomarkers assessed at baseline and follow‐up. Because the main trial analyses demonstrated significant target to background ratio decreases with both treatment strategies but no difference across treatment groups, we analyzed all patients together. Baseline values of serum amyloid A, C‐reactive protein, soluble tumor necrosis factor receptor 1, adiponectin, YKL‐40, and osteoprotegerin were associated with significant change in target to background ratio. When selected candidate biomarkers were added to the clinical variables, the adjusted R2 improved from 0.20 to 0.33 (likelihood ratio P=0.0005). Conclusions A candidate biomarker approach identified several promising biomarkers that associate with baseline and treatment‐associated changes in arterial inflammation in patients with RA. These will now be tested in an external validation cohort.